2008
DOI: 10.1002/cbf.1475
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative comparison of PTH1R in breast cancer MCF7 and osteosarcoma SaOS‐2 cell lines

Abstract: The aim of the present study was to compare the classical parathyroid hormone/parathyroid hormone-related peptide (PTH/PTHrP) receptors in MCF7 breast cancer cells with SaOS-2 osteosarcoma cell line. Quantitative binding showed that (125)I-PTHrP-1-34(Tyr) binds with a single binding site in both cells. However (125)I-PTHrP-1-34(Tyr) has higher affinity binding in MCF7 (K(D) = 1.88 +/- 0.08 nM) than in SaOS-2 cells (K(D) = 4.4 +/- 0.185 nM). The competitive binding using 3.3 nM (125)I-PTHrP-1-34(Tyr) with incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
2
3
0
Order By: Relevance
“…Consequently, a cAMP immunoassay showed activation of the cAMP/PKA pathway through human N‐terminal PTH, N‐terminal PTHrP, but not through the C‐terminal PTHrP fragment. These results are in accordance with recent publications which show that breast cancer (MCF7) and osteosarcoma cells (Saos‐2) frequently express PTH1R 20, 21…”
Section: Resultssupporting
confidence: 93%
“…Consequently, a cAMP immunoassay showed activation of the cAMP/PKA pathway through human N‐terminal PTH, N‐terminal PTHrP, but not through the C‐terminal PTHrP fragment. These results are in accordance with recent publications which show that breast cancer (MCF7) and osteosarcoma cells (Saos‐2) frequently express PTH1R 20, 21…”
Section: Resultssupporting
confidence: 93%
“…These results are in accordance with recent publications which show that breast cancer (MCF7) and osteosarcoma cells (Saos-2) frequently express PTH1R. 20,21 Both PTHrP fragments, N-and C-terminal PTHrP, significantly inhibited apoptosis of Saos-2 cells treated with chemotherapeutic drugs. N-terminal PTHrP inhibited doxorubicin-, mitoxantroneand bleomycin-induced apoptosis, whereas C-terminal PTHrP repressed doxorubicin-and bleomycin-induced apoptosis but not mitoxantrone-induced apoptosis (Fig.…”
Section: Pthrp Inhibits Apoptosis Induced By Chemotherapeutic Agentssupporting
confidence: 92%
“…It cooperates with extracellular calcium sensitive receptors (CaSR) to maintain the physiological homeostasis of extracellular calcium ions (Ca2 + ) and lactation. It can promote the proliferation of breast cancer and is closely related to the bone metastasis of breast cancer ( Alokail and Peddie 2008 ; Dittmer et al, 2006 ; Liang et al, 2012 ; Yang and Wang 2018 ). Some studies in GC have shown that PTH1R can be expressed in some gastric cancer cell lines, and reduced PTH1R expression can promote gastric hypergastrinemia and gastric neuroendocrine tumors ( Al Menhali et al, 2017 ; Calvete et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%